Production of Hydrogen with Electrolysis-Photovoltaic from Seawater Using Ni-Mo Electrodes Deposited at Cu (Ni-Mo/Cu) - Nabilah, Shafa; Salbila Marhaenetry, Hanun; Maftuha Prizantika, Mepa; Tarbiyatun Nasyin Maleiva , Lalak (ASEAN Journal of Chemical Engineering, 2025)
The energy crisis and environmental impacts of fossil fuels encourage the development of environmentally friendly alternative energy sources. Hydrogen is a promising candidate as a future energy carrier. This research aims to optimize hydrogen production through seawater electrolysis using Ni–Mo/Cu electrodes with a photovoltaic energy source. Ni–Mo/Cu electrodes were prepared via electrodeposition at a varied durations of 2, 4, and 6 minutes. Electrode characterization was conducted using X-Ray Diffraction (XRD) and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM–EDX). Photovoltaic systems were designed using fuzzy logic to optimize solar energy absorption. The electrolysis process was carried out at voltages of 10–30 V. The results showed that a 4-minute electrodeposition produced the most significant Ni–Mo layer. The highest hydrogen production rate of 0.7417 cm³/s was obtained at 25 V using a Ni–Mo/Cu electrode. These findings demonstrate the feasibility of producing hydrogen from seawater using renewable energy sources under the studied conditions.